Before Jutland : the naval war in Northern European waters, August 1914-February 1915 - Goldrick, James (Naval Institute Press, 2015)
Before Jutland is an effort to understand what happened at sea in northern European waters in 1914-15 when the German High Sea Fleet faced the Grand Fleet in the North Sea and the Russian Fleet in the Baltic. The book is an extensively revised and extended version of the author's 1984 work The King's Ships Were at Sea. It covers the first six months of the First World War because very important things occurred in that time and, despite the loose ends that inevitably remain with four more years of conflict to follow, important things can be said. The focus is primarily on the British, but both.